(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of H1 blocker, H2 blocker, corticosteroid in combination or individually in resolution of the sign and symptoms of acute urticaria. Study Design: Randomized control trial Place and Duration of Study: This study was carried out at Medical Department, Naseer Teaching Hospital, Peshawar, Khyber Pakhtunkhwa (KPK) for the period of six months (July 2012 through December 2012). Materials and Methods: In this study 140 adult patients of both gender with acute urticaria were treated with either H1 blocker (group A), H2 blocker ( group B) or in combinations of H1 blocker + H2 blocker (group C), H1blocker + H2 blocker + dexamethasone (group D), H1 blocker + dexamethasone (Group E), H2 blocker + dexamethasone (Group F) or Dexamethasone (group G) alone. The end points were resolution of sign and symptoms in each group of patients (minimum 3 hours after treatment). Pregnant females, anemic and Patients with cardiac disease were excluded. Results: H1+ H2blockers + dexamethasone found to be most effective therapeutic combination (95% of patients) in resolution of sign and symptoms of acute urticaria, followed by H1 blocker + dexamethasone (90%) and H1+ H2 blockers (85%). Conclusion: This study concludes that the combination of H1+H2 blockers + dexamethasone is more effective in relieving the patient from the sign and symptom of acute urticaria as compared to H1blocker or H2 blocker or dexamethasone given alone or in combination of any two.